A workforce survey of Australian osteopathy: analysis of a nationally-representative sample of osteopaths from the Osteopathy Research and Innovation Network (ORION) project - Jon Adams; David Sibbritt; Amie Steel; Wenbo Peng (BMC Health Services Research, 2018)
Abstract Background Limited information is available regarding the profile and clinical practice characteristics of the osteopathy workforce in Australia. This paper reports such information by analysing data from a nationally-representative sample of Australian osteopaths. Methods Data was obtained from a workforce survey of Australian osteopathy, investigating the characteristics of the practitioner, their practice, clinical management features and perceptions regarding research. The survey questionnaire was distributed to all registered osteopaths across Australia in 2016 as part of the Osteopathy Research and Innovation Network (ORION) project. Results A total of 992 Australian osteopaths participated in this study representing a response rate of 49.1%. The average age of the participants was 38.0 years with 58.1% being female and the majority holding a Bachelor or higher degree qualification related to the osteopathy professional. Approximately 80.0% of the osteopaths were practicing in an urban area, with most osteopaths working in multi-practitioner locations, having referral relationships with a range of health care practitioners, managing patients a number of musculoskeletal disorders, and providing multi-model treatment options. Conclusions A total of 3.9 million patients were estimated to consult with osteopaths every year and an average of approximate 3.0 million hours were spent delivering osteopathy services per year. Further research is required to provide rich, in-depth examination regarding a range of osteopathy workforce issues which will help ensure safe, effective patient care to all receiving and providing treatments as part of the broader Australian health system.